2013
DOI: 10.5005/jp-journals-10008-1132
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure rise after Anti-VEGF Treatment: Prevalence, Possible Mechanisms and Correlations

Abstract: Intraocular pressure (IOP) rise after anti-vascular endothelial growth factor (VEGF) treatment for neovascular age-related macular degeneration (AMD) can be either short-term or long-term and may require medical intervention. Short-term IOP spikes are a fairly common and well recognized complication of anti-VEGF injections. Long-term IOP rise is less well-understood and disputed as a complication by some authors. We try to review current literature on the subject and especially studies focused on the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
0
25
2
2
Order By: Relevance
“…However, information regarding long-term increase in IOP is varied in the literature [ 34 ]. Kampougeris and colleagues define a raise in IOP as an increase up to 5 mmHg from baseline [ 35 ]. In our study, the values of IOP were within the normal limits at all timepoints, and ± 1 mmHg changes in mean IOP scores were seen from baseline to most timepoints; these changes were not significant, consistent with the aforementioned statement.…”
Section: Discussionmentioning
confidence: 99%
“…However, information regarding long-term increase in IOP is varied in the literature [ 34 ]. Kampougeris and colleagues define a raise in IOP as an increase up to 5 mmHg from baseline [ 35 ]. In our study, the values of IOP were within the normal limits at all timepoints, and ± 1 mmHg changes in mean IOP scores were seen from baseline to most timepoints; these changes were not significant, consistent with the aforementioned statement.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained intraocular pressure rise following intravitreal anti-VEGF injections is a known phenomenon, with several publications addressing this issue in part or whole [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…ere is a certain measure of discrepancy in reporting insofar as the potential risk factors as well as definitions of intraocular pressure (IOP) rise are concerned [6][7][8]. With numerous publications on the subject, it is only natural that contrasting outcomes are noted in studies conducted across the globe [1][2][3][4][5][6][7][8], the most disputed amongst risk factors for IOP rise being the number of injections administered and the treatment interval [2] between consecutive injections. When one factor in the indication, the anti-VEGF agent used, the phakic status, the anterior chamber angle status, family history of glaucoma, and other characteristics [1,2], it is evident that the condition (IOP rise) and analysis thereof is a complex phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The intraocular pressure (IOP) rise occurring after this procedure revealed to be transient and usually normalizes spontaneously within 30 minutes; 6 - 8 however, repeated IOP spikes may be a contributing factor for sustained IOP elevation in susceptible eyes, related to the trabecular meshwork damage. 8 9 The presence of vitreous reflux has been associated with lower postinjection IOP 10 and Pang et al 11 reported that the incidence of vitreous reflux was higher with larger bore size needles. Hence, we hypothesize that larger 27-gauge needles are less associated with IOP spikes, as they may cause higher vitreous reflux.…”
Section: Introductionmentioning
confidence: 99%